Family cohesion, acculturation, maternal cortisol, and preterm birth in Mexican-American women - Ruiz RJ; Pickler RH; Marti CN; Jallo N (Dove Medical Press, 2013)
R Jeanne Ruiz,1 Rita H Pickler,2 C Nathan Marti,3 Nancy Jallo41College of Nursing, The Ohio State University, Columbus, OH, USA; 2Department of Patient Services, Cincinnati Children's Hospital Medical Center, Cincinnati, OH, USA; 3Abacist Analytics, Austin, TX, USA; 4School of Nursing, Virginia Commonwealth University, Richmond, VA, USAObjective: To examine the potential moderating effects of family cohesion and acculturation on the physiological stress response (cortisol) as a predictor of preterm birth (PTB) in pregnant Mexican-American women.Methods: The sample included 470 participants; 33 had preterm births. All participants were self-identified as Mexican-American. In this cross-sectional study, family cohesion was measured by a self-report questionnaire. Acculturation was measured by self-report questionnaire as well as by years in the United States and country of birth. Stress was measured by serum cortisol. All measures were obtained at 22—24 weeks gestation. Additional data including history of PTB were obtained from the health record. Data analysis was primarily conducted using logistic regression.Results: The relationship between stress and PTB was predicted by family cohesion (estimate/standard error [E/SE] = —2.46, P = 0.014) and acculturation (E/SE = 2.56, P = 0.011). In addition, there was an interaction between family cohesion and history of previous PTB (E/SE = —2.12, P = 0.035).Conclusion: Results indicate that the impact of cortisol on PTB is predicted by acculturation and family cohesion such that higher levels of cortisol in conjunction with higher levels of acculturation and lower levels of family cohesion are associated with increased risk of PTB. In addition, low family cohesion in combination with a history of PTB was associated with higher levels of PTB. Assessment of family cohesion, including problem solving, adherence to family decisions, family shared space, and activity, should be included as part of prenatal assessment for risk of PTB. Subsequently, interventions that focus on improving the individual's response to an imbalance in family functioning are needed. In addition, prenatal assessment of level of acculturation may also identify those who are at risk for PTB.Keywords: preterm birth, cortisol, family cohesion, Mexican-American, stress, acculturation